ANTIPLATELET THERAPY CONTROL: CREDIBILITY GAP OR SEARCH FOR NEW DECISIONS? - Yu. I. Grinshtein; A. A. Kosinova; I. Yu. Grinshtein (Рациональная фармакотерапия в кардиологии)
The review presents recent data on the usage of platelet functional tests in patients with ischemic heart disease after percutaneous coronary intervention and its contribution to antiplatelet therapy personalization and cardiovascular events frequency reduction.